A wafer mapping technique for residual stress in surface micromachined films. (20th July 2016) - Schiavone, G; Murray, J; Smith, S; Desmulliez, M P Y; Mount, A R; Walton, A J
Abstract: The design of MEMS devices employing movable structures is crucially dependant on the mechanical behaviour of the deposited materials. It is therefore important to be able to fully characterize the micromachined films and predict with confidence the mechanical properties of patterned structures. This paper presents a characterization technique that enables the residual stress in MEMS films to be mapped at the wafer level by using microstructures released by surface micromachining. These dedicated MEMS test structures and the associated measurement techniques are used to extract localized information on the strain and Young's modulus of the film under investigation. The residual stress is then determined by numerically coupling this data with a finite element analysis of the structure. This paper illustrates the measurement routine and demonstrates it with a case study using electrochemically deposited alloys of nickel and iron, particularly prone to develop high levels of residual stress. The results show that the technique enables wafer mapping of film non-uniformities and identifies wafer-to-wafer differences. A comparison between the results obtained from the mapping technique and conventional wafer bow measurements highlights the benefits of using a procedure tailored to films that are non-uniform, patterned and surface-micromachined, as opposed to simple standard stress extraction methods. The presented technique reveals detailed information that is generally unexplored when using conventional stress extraction methods such as wafer bow measurements.